2021
DOI: 10.6060/mhc210440e
|View full text |Cite
|
Sign up to set email alerts
|

Triacetate of Benzoazacrown Compound as a Chelator for Lead Cations Promising for Targeted Radiopharmaceuticals

Abstract: Triacetate of 15-benzoazacrown-5 compound (H 3 BA3A) is a new ligand that has shown advantages towards chelation of some cations. In this paper H 3 BA3A was consequently studied for binding of lead cation. With respect to nuclear properties of 212 Pb radioisotope it can be used for therapy of various oncological diseases mainly due to alpha-emitting daughter radionuclide 212 Bi. Complexes of such radionuclides are considered as parts of targeted radiopharmaceuticals that can be conjugated with biomolecules t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the nine-fold excess of fetal bovine serum, both complexes of [ 64 Cu]Cu BA2A1Py and [ 210 Pb]Pb BA2A1Py have shown a lack of radionuclide loss during 4 h and 2 days, respectively ( Figure 7 ). Comparing the obtained data with earlier published results on complexes with BA3A 3− [ 7 , 8 ] it is evident that, despite close complexation constants for CuBA3A and Cu BA2A1Py , the stability of the latter radiolabeled chelate is higher. This showed up even after 1 h of incubation and was well pronounced after 4 h. Wherein, both complexes of Pb 2+ are stable after 2 days of incubation despite more than one order of difference of logβ ( Table 1 ).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…In the nine-fold excess of fetal bovine serum, both complexes of [ 64 Cu]Cu BA2A1Py and [ 210 Pb]Pb BA2A1Py have shown a lack of radionuclide loss during 4 h and 2 days, respectively ( Figure 7 ). Comparing the obtained data with earlier published results on complexes with BA3A 3− [ 7 , 8 ] it is evident that, despite close complexation constants for CuBA3A and Cu BA2A1Py , the stability of the latter radiolabeled chelate is higher. This showed up even after 1 h of incubation and was well pronounced after 4 h. Wherein, both complexes of Pb 2+ are stable after 2 days of incubation despite more than one order of difference of logβ ( Table 1 ).…”
Section: Resultssupporting
confidence: 76%
“…Taking into account the changes in the stability constants with the cations considered, it is expedient to compare the stabilities of radiolabeled complexes of BA2A1Py 2− with Cu 2+ and Pb 2+ in the competing medium, such as serum proteins, because BA3A 3− complexes of Cu 2+ and Pb 2+ have shown that only the latter was stable enough in this challenging environment, despite the close values of logβ [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations